SOFT AND HARD PIEZOELECTRIC MATERIALS FOR THE CONSTRUCTION OF A PIEZOELECTRIC SONOTRODE MOTOR (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2026)
The paper presents a comparative analysis of soft (PZT-5H) and hard (PZT-8) piezoceramic materials used in the construction of a piezoelectric sonotrode motor for ultrasonic-assisted extraction of plant compounds. The numerical models are two-dimensional and axially symmetric, and are analyzed at their natural and resonance frequencies by coupling the electric, structural, and acoustic fields. The effects of material and geometry, as quantified by a shape factor, on natural frequencies, absorbed power, and electrical impedance are investigated.
Keywords: Piezoelectric; Piezoelectric transducer; Piezoceramics; Sonotrode; Ultrasonic transducer